Avaliação do poder calorífico de resíduos sólidos urbanos e do seu potencial uso como combustíveis derivados de resíduos - Abreu, Dalton Mendes de (2024)
According to the "What a Waste 2.0"report published in 2018 by the World Bank, approximately 2 billion tons of solid waste are generated annually on our planet, of which 33% do not receive proper treatment, posing a risk to the environment. The report also projects a 70% increase in solid waste generation over the next 30 years. Countries in Western Europe, Japan, and Korea have been employing technologies to promote waste reduction, recycling, and controlled incineration for energy recovery, minimizing environmental impacts and bringing economic and social benefits. Despite the progress made in other countries, in Brazil, around 39% of collected waste was improperly disposed of, with emphasis on the Northern and Northeastern regions, where only 37% of the collected waste was sent for proper environmental disposal, causing environmental issues and wastage of valuable resources. In this context, this study aims to evaluate the calorific value of samples from bicycle tires, tire treads and sidewalls, leaves, peels, and seeds of Neem, peels, leaves, and wood chips of cashew trees, carob wood chips, chestnut peels, Pinus spp slats, and composite plastic filaments made of polylactic acid to classify and identify which of these wastes have the potential for energy generation and application in industrial processes. The analysis of higher calorific value was conducted using an IKA C200 bomb calorimeter and then the lower calorific value was estimated. Among the analyzed samples, only Neem leaves showed a low lower calorific value (6.584 MJ/kg), while bicycle tire fractions (31.706 MJ/kg), tire tread (35.948 MJ/kg), and car tire sidewalls (31.876 MJ/kg), Neem seeds (20.594 MJ/kg), and chestnut peels (22.015 MJ/kg) fell under class P1. Carob wood chips (16.621 MJ/kg), cashew wood chips (16.485 MJ/kg), Pinus spp slats (15.967 MJ/kg), and polylactic acid filament (18.396 MJ/kg) fell under class P2, and Neem peels (14.865 MJ/kg) and cashew leaves and peels (13.449 MJ/kg) were categorized under class P3 according to NBR 16849:2020, showing potential for use as waste-derived fuels in industrial boilers, pyrolysis and gasification processes, and in clinker production furnaces according to Resolution SIMA No. 047, dated August 6, 2020, considering the calorific value parameter.